Macroprudential Policies, Economic Growth, and Banking Crises - Belkhir, Mohamed (IMF Working Papers; Working Paper ;, 2020)
Using a sample that covers more than 100 countries over the 2000-2017 period, we assess the impact of macroprudential policies on financial stability. In particular, we examine whether the activation of macroprudential policies is conducive to a lower incidence of systemic banking crises. Our empirical setup is designed to account for the potential direct and indirect effects that macroprudential policies can have on banking crises. We find that while macro-prudential policies exert a direct stabilizing effect, they also have an indirect destabilizing effect, which works through the depressing of economic growth. A Generalized Impulse Response Function analysis of a dynamic system composed of the probability of a banking crisis and economic growth reveals, however, that macroprudential policies have a positive net effect on financial stability (lower likelihood of systemic banking crises).